Improving the new product development using big data: a case study of a food company. Issue 11 (17th September 2019) - Jagtap, Sandeep; Duong, Linh Nguyen Khanh
Abstract : Purpose: Recently, the concept of big data (BD) has evolved and started to play an essential role in the advancement of new product development (NPD) in various sectors contributing to value creation, idea generation and competitive advantage. However, limited research has been done on how the food industry can exploit BD to improve the processes involved in NPD. The purpose of this paper is to understand the use of BD in new food product development. It helps to find relevant information and integrate sustainability to the early stages of the NPD process in the food industry. Design/methodology/approach: This research illustrates a case study of a beverage company wherein they used BD analytics to support their NPD team to launch a two-litre lemonade drink in the market for their retailer with less than 5 g sugar per 100 ml in the shortest possible time. Findings: The use of BD helps to reduce NPD costs and time without affecting the taste and on par with competitor's products. Originality/value: The research can support NPD professionals through the application of BD analytics to bring products at lower costs to the market as quickly as possible.